Race‐based and sex‐based differences in bioactive lipid mediators after myocardial infarction. (4th May 2020) - Halade, Ganesh V.; Kain, Vasundhara; Dillion, Chrisly; Beasley, Mark; Dudenbostel, Tanja; Oparil, Suzanne; Limdi, Nita A.
Abstract: Aims: Leucocyte‐directed specialized pro‐resolving mediators (SPMs) are essential for cardiac repair, and their biosynthesis coincides with the expression of pro‐inflammatory mediators; however, the precise quantitation during an acute myocardial infarction (MI) event is poorly understood in race‐specific and sex‐specific manner. Coronary heart disease is the leading cause of death and disability in the USA. Although the prevalence of coronary heart disease is similar between Black and White patients, cardiovascular events (including MI), rehospitalization, and mortality are disproportionately higher in Black patients. Therefore, understanding differences in inflammation and resolution can enable the development of predictive, personalized, and precise treatment and attenuate sex/racial disparities. Thus, herein, we assess differences in bioactive lipids and SPMs, between Black and White patients experiencing an acute MI. Methods and results: From the PRiME‐GGAT cohort, we collected plasma after MI within 24–48 h from 22 Black (15 male and 7 female) and 31 White (23 male and 8 female) subjects for a comparative race‐based and sex‐based analyses. MI was confirmed using a biochemical measurement of plasma troponin and ST elevation. Plasma levels of three essential polyunsaturated fatty acids [arachidonic acid (AA), docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA)] and a set of 40 bioactive lipid mediators with major emphasis on SPMs were quantified by liquid chromatography–mass spectrometry. AA and DHA were higher in White male and female patients, and EPA was noted higher only in White male patients compared with White female and Black male and female patients. Lipoxygenase‐mediated AA‐derived 12‐hydroxyeicosatetraenoic acid (29–63%) and 15‐hydroxyeicosatetraenoic acid (3–9%) and DHA‐derived 17‐hydroxydocosahexaenoic acid (3–22%) and 14‐hydroxydocosahexaenoic acid (7–10%) were major bioactive lipid mediators in plasma. The SPM signature resolvin E1 was significantly lower in Black patients compared with White male and female patients, whereas protectin D1 was lower in White male patients compared with White female and Black male and female patients. Conclusion: Our comparative analyses of fatty acids and respective cyclooxygenase‐derived and lipoxygenase‐derived SPM signatures capture the heterogeneity of disease pathology and elucidate potential mechanisms underlying sex‐based and race‐based differences following MI.